The effects of financial factors on Peruvian mining companies share price - Carhuamaca-Floresa, Almendra (2021)
This research analyses the relationship and relative importance of financial factors on the Peruvian mining copper companies´ share prices from 2010 to 2018. Voting common share prices were focused and book value, dividend per share, dividend yield, price earnings, earnings per share and roe were employed as regressors. Fixed-effects regression was used, and tests of stationarity, distribution, and specification harnessed. It was found that earnings per share and dividend yield had a positive and significant relationship with share prices, while book value had a negative one.